CREATION OF MULTILAYERED KERATINOCYTE SHEET ON COLLAGEN FROM HUMAN AMNIOTIC MEMBRANE - Hà, Trần Lê Bảo; Toại, Trần Công; Sơn, Hoàng Nghĩa (Vietnam Journal of Biotechnology, 2011)
Epidermis composed of terminally differentiated  stratified  squamous epithelium  is the outermost  layer of the  skin.  The epidermis  is the major  barrier protect  the  body from inhospitable  environment  factors  such  as biological,  chemical,  physical  factors.  Epidermis  which  consists  of  the  multilayered  keratinocytes  could  be created  in vitro for  the freatment of  acute burn  injuries  and  chronic  wounds. In  this  study, the  multilayered keratinocyte  sheets  were  created from the  adult  human  keratinocytes  and  the  amniotic  collagen  membrane. Human  keratinocytes  were  isolated,  cultured,  amplified  in  seram  free  medium. Collagen  membrane  was derived from human amniotic membrane of which the epithelium was removed and evaluated by HE staining. After  subcultured on collagen membrane, keratinocytes were stimulated  for proliferation  and differentiation  to create multilayer by airlifting.  The multilayered keratinocyte sheet characteristics were evaluated by using RT-PCR  and immunohistochemistry.  The results  showed that  epithelial  cells were removed  completely from the human  amniotic membrane  by enzyme  and mechanical  treating. Keratinocytes  proliferated  and  formed  4 - 5 layers on collagen. They also expressed some differentiation  and proliferation  markers at 7 days after  airlifting. The keratinocytes which were positive with proliferative  marker (p63) lied closely on the collagen membrane and upper ofthe  cells  differentiated.